Priest learned and enlightened in Peter I’s reform program - Kuczyńska, Marzanna (Poznańskie Studia Slawistyczne, 2018)
The article is an attempt to define the notions of wisdom and enlightenment which were practised by the clergy in Peter the First’s time. For that reason, the notions’ components alike world view, knowledge, skills, and personal pattern have been examined in order to demonstrate that they were founded chiefly on the enlightenment ideas. According to the undertaken analysis, however, it has turned out that they also were strongly adapted to the Russian political conditions. Due to this, the commented notions cannot be explicitly formulated, since they are of a complex character resulted from the programme of utility serving the country.